“CARACTERIZACIÓN DE LA CADENA DE VALOR DEL CAFÉ BAJO LA MODALIDAD INDEPENDIENTE Y ASOCIATIVA EN EL CANTÓN PALANDA, PROVINCIA DE ZAMORA CHINCHIPE, PERIODO 2020-2021. - Carrión Sarmiento, Karina Geovanna (2021)
The present research whose general objective was to characterize the coffee value chain under the independent and associative modality in the Palanda canton, Zamora Chinchipe province, in the period 2020-2021. The Value Links Methodology, non-probabilistic sampling for convenience and the snowball were used and 49 actors were surveyed, the results obtained show that the value chain of the independent modality has the links of: provision, production, storage, commercialization and consumption, while the associative modality is made up of provision, production, storage, transformation, commercialization and consumption. It was determined that both independent and associated producers are the actors that generate the greatest value because they carry out the sowing, care, harvesting and post-harvest processes, and this is where the quality of the coffee is determined. The associate producer exports the coffee to international markets while the independent producer sells his products locally at too low prices. Likewise, despite the fact that education is considered one of the most important aspects for the innovation of production systems, it was determined that 80% of producers have a primary education level, for this reason a restructuring of the value chain of Both modalities reducing intermediaries and focusing on the producer, raising the education levels in the producers as well as in the independent modality, consider selling the coffee to international markets.